Hypomorphic Notch 3 Alleles Link Notch Signaling to Ischemic Cerebral Small-vessel Disease (2011)
ABSTRACT: The most common monogenic cause of small-vessel disease leading to ischemic stroke and vascular dementia is the neurodegenerative syndrome cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), which is associated with mutations in the Notch 3 receptor. CADASIL pathology is characterized by vascular smooth muscle cell degeneration and accumulation of diagnostic granular osmiophilic material (GOM) in vessels. The functional nature of the Notch 3 mutations causing CADASIL and their mechanistic connection to small-vessel disease and GOM accumulation remain enigmatic. To gain insight into how Notch 3 function is linked to CADASIL pathophysiology, we studied two phenotypically distinct mutations, C455R and R1031C, respectively associated with early and late onset of stroke, by using hemodynamic analyses in transgenic mouse models, receptor activity assays in cell culture, and proteomic examination of postmortem human tissue. We demonstrate that the C455R and R1031C mutations define different hypomorphic activity states of Notch 3, a property linked to schemic stroke susceptibility in mouse models we generated. Importantly, these mice develop osmiophilic deposits and other age-dependent phenotypes that parallel remarkably the human condition. Proteomic analysis of human brain vessels, carrying the same CADASIL mutations, identified clusterin and collagen 18 α1/endostatin as GOM components. Our findings link loss of Notch signaling with ischemic cerebral small-vessel disease, a prevalent human condition. We determine that CADASIL pathophysiology is associated with hypomorphic Notch 3 function in vascular smooth muscle cells and implicate the accumulation of clusterin and collagen 18 α1/endostatin in brain vessel pathology.